2014
DOI: 10.4103/2277-9175.124668
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low-frequency electromagnetic field influences the survival and proliferation effect of human adipose derived stem cells

Abstract: Background:Extremely low-frequency electromagnetic fields (ELF-EMF) can effect on biological systems and alters some cell functions like proliferation rate. Therefore, we aimed to attempt the evaluation effect of ELF-EMF on the growth of human adipose derived stem cells (hADSCs).Materials and Methods:ELF-EMF was generated by a system including autotransformer, multi-meter, solenoid coils, teslameter and its probe. We assessed the effect of ELF-EMF with intensity of 0.5 and 1 mT and power line frequency 50 Hz o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 34 publications
1
18
1
Order By: Relevance
“…A critical issue that had to be taken into consideration in designing this in vitro study was to maximize the cell exposure to the field. In fact, several authors have shown that the electrical field depends on the cross-sectional area of the culture media seen by the magnetic field [ 27 29 ]. Therefore, in this study, the PST® treatment was performed by placing the cell culture plate at the center of the PST® device, parallel to the ground, in order to have the magnetic field vector perpendicular to the plate surface.…”
Section: Discussionmentioning
confidence: 99%
“…A critical issue that had to be taken into consideration in designing this in vitro study was to maximize the cell exposure to the field. In fact, several authors have shown that the electrical field depends on the cross-sectional area of the culture media seen by the magnetic field [ 27 29 ]. Therefore, in this study, the PST® treatment was performed by placing the cell culture plate at the center of the PST® device, parallel to the ground, in order to have the magnetic field vector perpendicular to the plate surface.…”
Section: Discussionmentioning
confidence: 99%
“…hASCs proliferation and survival were enhanced by PEMFs treatment [52]. Moreover, in combination with chondrogenic inductive medium, PEMFs were able to increase ASCs chondrogenic differentiation, in terms of expression of Sox9, collagen type I and II, aggrecan and osteocalcin, as well as mineralized matrix, and glycosaminoglycans deposition [53].…”
Section: Pulsed Electromagnetic Fieldmentioning
confidence: 99%
“…According to recent literature, ELF‐MF exposure is believed to play a role in the later stages (promotion and progression) of tumorigenesis, especially in brain‐derived tumors (Poulletier de Gannes et al, ; Turner et al, ). Critical cellular pathways and functions have been proposed as targets of ELF magnetic fields: DNA damage profile (Panagopoulos et al, ; Villarini et al, ; Yoon et al, ), proliferation and/or survival dynamics (Martínez et al, ; Trillo et al, ; Razavi et al, ), signaling pathways (Nie and Henderson, ; Patruno et al, ), and redox balance (Falone et al, ; Falone et al, ; Di Loreto et al, ; Mattsson and Simkó, ). We have previously shown that the exposure to an ELF magnetic field increases the proliferation of cells isolated from neuroblastoma, and this was linked to the novel expression of protein associated to a more malignant phenotype (Sulpizio et al, ).…”
mentioning
confidence: 99%